2018
DOI: 10.21873/cgp.20106
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Susceptibility Gene 101 Mediates Anoikis Resistance of Metastatic Thyroid Cancer Cells

Abstract: Background/Aim: Resistance to anoikis is a prerequisite step in metastasis, a major cause of death in patients with cancer, including thyroid cancer. Impairing anoikis resistance is a possible strategy for therapy of metastatic cancer. We, therefore, we aimed to investigate the key players of anoikis resistance. Materials and Methods: Papillary-type (BCPAP), follicular-type (FTC133), and anaplastic-type (ARO) thyroid carcinoma cells, cultured in poly(2-hydroxyethyl methacrylate)-coated plates to mimic circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…Here, we demonstrated that cancer-specific byproduct TSG∆154-1054 stabilizes TSG101 protein, and thus it promotes tumor cell aggression in terms of proliferative, migratory, and metastatic activities. Recent TSG101 knockdown experiments implicated the function of TSG101 protein in anoikis (cell-detachment-induced apoptosis) resistance of thyroid cancer, which is a prerequisite for metastasis [42]. It is of interest to examine the activation of anoikis in TSGΔ154-1054-siRNA transfected cells in which TSG101 protein is upregulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we demonstrated that cancer-specific byproduct TSG∆154-1054 stabilizes TSG101 protein, and thus it promotes tumor cell aggression in terms of proliferative, migratory, and metastatic activities. Recent TSG101 knockdown experiments implicated the function of TSG101 protein in anoikis (cell-detachment-induced apoptosis) resistance of thyroid cancer, which is a prerequisite for metastasis [42]. It is of interest to examine the activation of anoikis in TSGΔ154-1054-siRNA transfected cells in which TSG101 protein is upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest to examine the activation of anoikis in TSGΔ154-1054-siRNA transfected cells in which TSG101 protein is upregulated. Since we found no activation of caspase 8 in these knockdown cells, a proapoptotic protein (BCL-2 like protein 4) and an apoptotic marker (cleaved poly-ADP ribose polymerase) may function in anoikis [42] through caspase 8-independent pathways.…”
Section: Discussionmentioning
confidence: 99%
“…All these proteins have been involved in different metastatic processes, and could be a target for new therapies but, more interestingly, they can be indicators of the process' progress and could suggest what the mechanism and the signalling pathway of these cells involved in the resistance to chemotherapeutic treatments is. One of the cellular mechanisms that may be involved in these resistance processes is anoikis [24][25][26][27][28]. Anoikis is a form of apoptosis that occurs in anchorage-dependent cells and in a niche context, when the cells detach from the surrounding extracellular matrix (ECM) and lose the connection to the nurse surrounding cells [28,29]; this is one of the processes we observed after the combination of chemotherapy and treatment with the carboxy-terminal part of PEDF protein.…”
Section: Introductionmentioning
confidence: 89%
“…Furthermore, anoikis resistance has also been demonstrated to play an important role in metastatic thyroid cancer. Kittirat Saharat and colleagues have reported that tumor susceptibility gene 101 protein (TSG101) was identified to be upregulated in anoikis resistant thyroid cancer cells, which was accompanied with decreased expression of an apoptotic marker (cleaved poly-ADP ribose polymerase) and a pro-apoptotic protein (BCL-2 like protein 4) ( 8 ). Our previous study revealed that anoikis resistance induced by miR-424-5p promoted lung metastasis of thyroid cancer by inactivating Hippo signaling via simultaneously targeting WWC1, SAV1, and LAST2 ( 9 ).…”
Section: Introductionmentioning
confidence: 99%